Teachers' efforts in instilling student discipline in school discipline through pancasila education learning at smp negeri 8 malang - Fikri, Raihan Muhammad; Widodo, Rohmad; Prasetyo Wibowo, Arif (Universitas Tanjungpura, 2025)
This research aims to determine teachers' efforts in instilling student discipline towards school rules through learning Pancasila education at SMP Negeri 8 Malang. The location of this research was carried out at SMP Negeri 8 Malang. This research uses a qualitative approach with descriptive methods. The subjects in this research consisted of the Deputy Principal for Student Affairs, Civic Education Teachers and Students at SMP Negeri 8 Malang. The research procedure consists of the data collection process, reduction process, data presentation stage and drawing conclusions. Data and data sources such as primary data and secondary data. Several types of data collection techniques include observation, interviews and documentation. The research instruments are observation guidelines, interview guidelines and documentation guidelines. Data analysis techniques such as data collection, data reduction, data presentation, conclusions and verification. Then the final stage is data validity. The research results show that teachers apply various strategies, including socializing rules and using the QRStudent application to record violations. Pancasila education is integrated with disciplinary values, where teachers play an active role in enforcing regulations and providing appropriate sanctions. Supporting factors in instilling discipline include the quality of teacher human resources, the role of the OSIS, and parental support, while inhibiting factors come from the influence of students' interactions. Teachers' efforts to overcome these obstacles include warning procedures and personal approaches. The